Juridical and Constitutional Implications, Political Stability, and Institutional Effectiveness After the Constitutional Court’s Electoral Reform Decision - Setiadi, Ade; Muhafidin, Didin (International Journal of Science and Society, 2025)
This study aims to analyze the juridical and constitutional implications, political stability dynamics, and institutional effectiveness following the Constitutional Court’s decisions on electoral reform, particularly Decision 135/PUU-XXII/2024. Using a qualitative method with a doctrinal-normative and policy analysis approach, the research examines the effectiveness of Constitutional Court rulings in relation to political compliance, electoral system restructuring, and central–regional governance relations. The findings reveal that although Constitutional Court decisions are erga omnes, many non–self-executing rulings are only partially implemented due to the subordination of judicial authority to pragmatic political consensus between the Legislature and the Executive. The ruling on electoral separation offers administrative and humanitarian benefits and has the potential to strengthen regional representation and policy focus; however, it also produces significant risks, including the emergence of two major political cycles in close succession and heightened politicization of Acting Regional Heads during the 2–2.5 years transitional period. Furthermore, the effectiveness of the national Legislature and the Executive remain constrained by structural political fragmentation inherent in the proportional electoral system, whereas the separation of local elections contributes only marginally to improving the effectiveness of regional parliaments and does not resolve the broader issue of national political cohesion. The study concludes that the success of electoral reform depends on consistent enforcement of Constitutional Court rulings, coalition stability, and institutional designs capable of adapting to both national and regional political dynamics.